Research progress of natural silk fibroin and the application for drug delivery in chemotherapies - Yu, Bin; Li, Yanli; Lin, Yuxian; Zhu, Yuanying; Hao, Teng; Wu, Yan; Sun, Zheng; Yang, Xin; Xu, Hui (Frontiers in Pharmacology, 2023)
Silk fibroin has been widely used in biological fields due to its biocompatibility, mechanical properties, biodegradability, and safety. Recently, silk fibroin as a drug carrier was developed rapidly and achieved remarkable progress in cancer treatment. The silk fibroin-based delivery system could effectively kill tumor cells without significant side effects and drug resistance. However, few studies have been reported on silk fibroin delivery systems for antitumor therapy. The advancement of silk fibroin-based drug delivery systems research and its applications in cancer therapy are highlighted in this study. The properties, applications, private opinions, and future prospects of silk fibroin carriers are discussed to understand better the development of anti-cancer drug delivery systems, which may also contribute to advancing silk fibroin innovation.